(untitled) (Comparative & International Education Series, 2021)
Internationalization of universities has become a major strategy for university development driven by the need for global reputation along with enhanced revenue streams. Yet, though these internationalization efforts have increased in scope and depth in the last decade, the process has a long history in developing countries. In this chapter, I explore the evolution of the internationalization of higher education in Kenya paying close attention to the context in which it has been framed from the colonial era to the contemporary period. In the exploration, I demonstrate the manifest tension between the desire by universities to espouse global values and generate revenue as measures of success and advocate for the institutions to demonstrate local relevance even as they clamor for global ranking through internationalization. The analysis begins with the framing of higher education internationalization followed by the analysis of internationalization in the colonial, immediate post-independence, and the contemporary periods.